Shoushtary Diba in Sassanid Era: Production, Application and Quality - Yousefvand, Reza; Lotfizad, Roohalah; Khaksar, Mansour (Journal of History Culture and Art Research, 2018)
Since ancient times, Iran has been regarded as a bridge between East and West in terms of special geographical position. Meanwhile, some parts of the land were of particular importance because of their location on the Silk Road and the proximity to the center of government. Shoushtar is one of the ancient regions of Iran, which has been considered by various scholars and researchers from different aspects. In this paper, the historical background of Shoushtar and Diba Shoushtary, which has enjoyed a high economic value in the Sassanid era, has been studied. The aim of this paper is to investigate the historical, geographical, economic and commercial history of Shoushtar and the quality of its Diba, which is located as a geographic area along the southern route of the Silk Road and its most important product has been silk garment, of which the cover the Kaaba, the garments of the kings and rulers have been provided. The main issue of the research is based on this principle, which is the reason of the prosperity and quality of Shoushtari Diba.